Theoretical analysis, optimization, and experimental evaluation of dual function DP R-EDFA - Hossain, Nadir; Naji, A. W.; Mishra, V.; Abbou, F. M.; Abdul Rashid, Hairul Azhar; Faidz, A. R. (Springer, 2007)
A simple rate-equation model of double pass (DP), remotely-pumped Erbium-doped fiber amplifier (R-EDFA) is developed based on the Giles-and-Desurvire (1991) model of a single pass (SP) EDFA. The mathematical equations to calculate stimulated absorption-and-emission rate between levels 1 and 2 of SP EDFA are modified by integrating the reflected backward-propagating signal of the DP R-EDFA. Besides the signal amplification, dispersion compensation by the chirped-fiber Brag-grating (CFBG) inside the DP R-EDFA is also taken into account. The reflection losses of a signal by the CFBG are included in the backward-propagating signal of the DP R-EDFA. Considering a high gain and low noise figure (NF) by very low remote pump power as a main design objective, the design process of an optimized DP R-EDFA for a long haul optical-fiber-communication system (OFCS) is demonstrated. Robustness and stability of the DP R-EDFA rate-equation model developed are shown by analzing the numerical results and output shapes using various design parameters of the DP R-EDFA. Finally the DP R-EDFA, rate-equation model developed is validated with the help of experimental results.